Criterion for Distinguishing Sequential from Nonsequential Contributions to the Double Ionization of Helium in Ultrashort Extreme-Ultraviolet Pulses - Liu, Aihua; Thumm, Uwe (My University, 2015)
We quantify sequential and nonsequential contributions in two-photon double ionization of helium atoms by intense ultrashort extreme-ultraviolet pulses with central photon energies ℏωctr near the sequential double-ionization threshold. If the spectrum of such pulses overlaps both the sequential (ℏω>54.4 eV) and nonsequential (ℏω<54.4 eV) double-ionization regimes, the sequential and nonsequential double-ionization mechanisms are difficult to distinguish. By tracking the double-ionization asymmetry in joint photoelectron angular distributions, we introduce the two-electron forward-backward-emission asymmetry as a measure that allows the distinction of sequential and nonsequential contributions. Specifically, for ℏωctr=50 eV pulses with a sine-squared temporal profile, we find that the sequential double-ionization contribution is the largest at a pulse length of 650 as, due to competing temporal and spectral constraints. In addition, we validate a simple heuristic expression for the sequential double-ionization contribution in comparison with ab initio calculations.